The Diverse Functional Roles of Elongation Factor Tu (EF-Tu) in Microbial Pathogenesis - Harvey, Kate L.; Jarocki, Veronica M.; Charles, Ian G.; Djordjevic, Steven P. (Frontiers in Microbiology, 2019)
Elongation factor thermal unstable Tu (EF-Tu) is a G protein that catalyses the binding of aminoacyl-tRNA to the A-site of the ribosome inside living cells. Structural and biochemical studies have described the complex interactions needed to effect canonical function. However, EF-Tu has evolved the capacity to execute diverse functions on the extracellular surface of both eukaryote and prokaryote cells. EF-Tu can traffic to and is retained on, cell surfaces where can interact with membrane receptors and with extracellular matrix on the surface of plant and animal cells. Our structural studies indicate that short linear motifs (SLiMs) in surface exposed, non-conserved regions of the molecule may play a key role in the moonlighting functions ascribed to this ancient, highly abundant protein. Here we explore the diverse moonlighting functions relating to pathogenesis of EF-Tu in bacteria and examine putative SLiMs on surface-exposed regions of the molecule.